PENGARUH MUTU PELAYANAN ADMINISTRASI TERHADAP KEPUASAN PASIEN IGD DI PUSKESMAS PENIMBUNG TAHUN 2021 - Putra, Syatriawan Perdana; Desak Ketut Swaria Sari (Nusadaya Journal of Multidiciplinary Studies, 2022)
Puskesmas is the first strata health service unit in charge of organizing health efforts in a certain area, the health efforts carried out include promotive, preventive, curative and rehabilitative efforts. UPT BLUD Puskesmas Penimbung as one of the Puskesmas located in West Lombok Regency which serves outpatients. The quality of health services at puskesmas is the end product of complex interactions and dependencies between various components or aspects of service. Quality health center services will be one of the determining factors in efforts to improve public health status. The purpose of this study was to analyze the effect of the quality of administrative services on ER patient satisfaction at the Penimbung Public Health Center, in 2021. This type of research is an analytical study, namely research that aims to find the relationship between factors. The research approach used in this study was a cross sectional approach. The sample of this study was 87 respondents to the emergency department at the Penimbung Public Health Center. The results of this study indicate that there is a significant effect between service quality and patient satisfaction (p value = 0.000 < 0.05). The correlation results show that the higher the service quality, the higher the patient satisfaction.